スパイラル鋼管製造過程の違いによる残留応力のX線測定実験 - 薛, 迪緯; 田畑, 晶子; 杉浦, 邦征; 松本, 理佐; 北根, 安雄; 赤松, 伸祐 (Kou kouzou rombunshuu, 2025)
This paper studied residual stress distribution in spiral welding pipes applied to the Multi-Pipes Integrated Bridge Pier by X-ray experimental measurements. It is known that the residual stress will affect the fatigue life of the welding structures, therefore the residual stress due to the bending and welding manufacturing process needs to be evaluated. In this paper, the X-ray measurement was conducted to investigate the residual stress distribution of spiral welding pipes manufactured by two companies. The stress in the hoop, axial, vertical to the welding, and parallel to the welding direction of spiral welding pipes made by different companies, was studied to advance manufacturing management and collect mechanical data due to the bending and welding manufacturing process.